Large resignations and the demand for welfare - Iacono Quarantino, Pietro (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The pandemic years were marked, among many other things, by a great wave of voluntary resignations from work, not only in the USA, but also in Europe. A phenomenon that we believe to be related to the theme of well-being, understood as that state in which individuals are able to use their resources to cope with internal and external difficulties and to establish satisfying relationships.